Outcome of Early and Late Diagnosed Essex-Lopresti Injury. (21st June 2017) - Schnetzke, Marc; Porschke, Felix; Hoppe, Karin; Studier-Fischer, Stefan; Gruetzner, Paul-Alfred; Guehring, Thorsten
Abstract : Background: The aim of this study was to investigate the outcomes in a large series of Essex-Lopresti injuries (ELIs) and to compare patients with early and late diagnoses. Methods: Thirty-one patients with an ELI (average age and standard deviation [SD], 46 ± 10 years) who were followed for a minimum of 2 years were included in the study. Patients were grouped according to whether the ELI had been diagnosed early (on the day of the injury) or late (>4 weeks after the radial head injury). Acute treatment of early-diagnosed ELI included temporary stabilization of the distal radioulnar joint (DRUJ) by Kirschner wires with the forearm in supination for 6 weeks. Clinical outcomes were assessed on the basis of the range of motion, Mayo Elbow Performance Score (MEPS), Mayo Wrist Score (MWS), visual analog scale (VAS) score for wrist and elbow pain, and Disabilities of the Arm, Shoulder and Hand (DASH) score. Results: The ELI was diagnosed on the day of the injury in 16 patients (52%; the early group) and late (at a mean of 7 ± 7 months; range, 1 to 24 months) in 15 (48%; the late group). After a mean duration of follow-up of 5.3 ± 3.0 years (range, 2.0 to 13.1 years), patients with an early diagnosed ELI had significantly better clinical outcomes, compared with those with a late diagnosis, with regard to the MEPS (91.3 ± 8.7 versus 74.7 ± 15.3, p = 0.003), MWS (81.3 ± 16.5 versus 66.3 ± 17.6, p = 0.019), DASH score (12.5 ± 8.7 versus 45.3 ± 23.5, p = 0.001), VAS elbow pain score (0.7 ± 1.1 versus 3.3 ± 2.1, p = 0.001), and VAS wrist pain score (0.9 ± 1.2 versus 3.9 ± 1.7, p < 0.001). The ranges of motion of the elbow and wrist did not differ significantly between the early and late groups (p > 0.05). A significantly higher percentage of patients had complications or subsequent surgical procedures in the early than in the late group (38% [6 of 16] versus 93% [14 of 15], p < 0.001). Conclusions: Early diagnosis of an ELI with temporary stabilization of the DRUJ leads to satisfactory clinical mid-term results, whereas late diagnosis of an ELI is associated with a deteriorated outcome. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.